The Moderating Role of Technological Capabilities in the Relationship between Entrepreneurial Marketing and Firm Performance: A Qualitative Approach - Alfateh Fegada; Zoltan Veres (European Scientific Journal, ESJ, 2024)
Entrepreneurial marketing (EM) is a dynamic and innovative approach to marketing that is particularly well-suited for startups and small businesses. Thus, the study focuses on Sudanese SMEs in order to assist them in achieving profitability, sustainability, and competitive advantage in the long term. Consequently, our objectives are to develop the research pre-model and to explore in depth how entrepreneurs, managers, and employees of SMEs in Khartoum-Sudan are familiar with the concepts of the research pre-model, and how they can employ and take advantage of study concepts. To achieve these objectives, we relayed on the qualitative method an inductive approach to test the validity and to develop the research pre-model. Hence, we have designed an open-ended question scenario and conducted a certain interview utilizing multiple qualitative methods to gather the data from the purposive sample which consists of (15) individuals. We have divided the scenario into three main parts of questions, first open-ended questions about EM, in this regard the most important question that has been asked to the interviewees was “What are the factors/dimensions that comes to your mind when you hear about EM”? Secondly, open-ended questions about technological capabilities TCPs. “The commonly thought view of TCPs proposes that firms with strong technological capability can rapidly identify technological opportunities and the value of technological resources and utilizing modern equipment, in this scope benefits of entrepreneurial marketing should therefore be enhanced by a firm’s high technological capability”. e.g., “What are the expected advantages that will be rewarded by employing TCPs in SMEs”? Finally, we have grouped data into concepts, categories, and themes and then utilized a manual-thematic analysis as a method for identifying, analyzing, and interpreting patterns within data. In this scope we have analyzed the data and interpreted the results within three main themes. Accordingly, significant new dimensions have been discovered and generated which led to our final developed and adapted research model.